Real-world outcomes of pazopanib in metastatic soft tissue sarcoma: A retrospective Turkish oncology group (TOG) study - Bilici, Ahmet; Koca, Sinan; Karaağaç, Mustafa; Aydın Göktaş, Sabin; Eraslan, Emrah; Kaplan, Muhammed Ali; Ocak, Birol; Göksu, Sema Sezgin; Paydaş, Semra; Akgül, Fahri; Derin, Sümeyye; Ergün, Yakup (Springer, 2023)
Aim: Description of patient characteristics, effectiveness and safety in Turkish patients treated with pazopanib for metastatic soft tissue sarcoma (STS). Patients and methods: This multicenter study is based on retrospective review of hospital medical records of patients (? 18 years) treated with pazopanib for non-adipocytic metastatic STS at 37 Oncology clinics across Turkey. Objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS) and overall survival (OS) were evaluated with further analysis of data on the three most common histological subtypes (leiomyosarcoma [LMS], undifferentiated pleomorphic sarcoma [UPS], synovial sarcoma [SS]) in the cohort. Results: Data of 552 adults (57.6% women, median age: 52 years) were analyzed. DCR and ORR were 43.1% and 30.8%, respectively. Median PFS was 6.7 months and OS was 13.8 months. For LMS, UPS and SS, median PFSs were 6.1, 5.9 and 7.53 months and median OSs were 15.03, 12.87 and 12.27 months, respectively. ECOG ? 2 was associated with poor PFS and OS. Liver metastasis was only a factor for progression. Second-line use of pazopanib (vs. front-line) was associated with better PFS, its use beyond third line predicted worse OS. Adverse events (AE) occurred in 82.7% of patients. Most common AEs were fatigue (58.3%) and anorexia (52.3%) which were graded as ? 3 in 8.2% and 7.4% of patients, respectively. Conclusion: Pazopanib is effective and well-tolerated in treatment of non-adipocytic metastatic STS. Its earlier use (at second-line), good performance status may result in better outcomes. Worldwide scientific collaborations are important to gain knowledge on rarer STS subtypes by conducting studies in larger patient populations.
Keywords: Pazopanib; Soft Tissue Sarcoma; Targeted Therapy; Synovial Sarcoma; Leiomyosarcoma; Metastatic Soft Tissue Sarcoma